COUNSELING AND SCREENING FOR RISK FACTORS FOR HYPERCHOLESTEROLEMIA IN CLASS II A WOMEN'S CORRECTIONAL INSTITUTIONS BANDAR LAMPUNG CITY IN 2024 - Amirus, Khoidar; Muhani, Nova; Sari, Fitri Eka; ashari, Hernandi; Saputri, Firdha Azzahra; Terta, Riesca Lavenia (LPPM Univ. Ibn Khaldun Bogor, 2024)
The prevalence of hypercholesterolemia worldwide reaches around 45%. In the Southeast Asia region, the prevalence rate of hypercholesterolemia is around 30%, while in Indonesia it reaches 35%. Then the prevalence of high cholesterol levels in Lampung Province in 2018 reached 53.2%, this shows that in Lampung Province people with dyslipidemia are still high. The aim of this service is health screening and counseling to increase the knowledge of inmates regarding cholesterol disease. The service method is to carry out health screening such as checking blood pressure, weight, height and BMI then carrying out counseling activities related to preventing cholesterol disease. The service was carried out on January 19 2024 with a sample size of 235 inmates. at the Class IIA Women's Correctional Institution in Bandar Lampung City. The results of the service showed that those with good knowledge were 70.6% and those with poor knowledge were 29.4%. 21.7% of their families had a history of cholesterol and 78.3% of those did not have a history of cholesterol. experienced an increase in cholesterol levels by 72.8% and those who did not experienced an increase in cholesterol levels by 26.0%. had a BMI of very thin (0.9%), thin (69.8%), normal (22.1%) and fat (7.20%). The education level of the people who most often participate in this service is high school (66.0%). The people who most often participate in this service are aged 25-35 years (33.6%) and aged 36-45 years (32.3%). It is hoped that health workers can continue to improve health education and education regarding NCDs, especially cholesterol.